An Impressive Response to Zoldronic Acid Treatment for Chronic Recurrent Multifocal Osteomyelitis: A Case Report - Nabaa Ihsan Awadh FIBMS; Faiq I. Gorial CABMS, FIBMS; Khalid Burhan Khalid CABMS; Ahmed Dheyaa Al-Obaidi MBChB; Adil Saudi Khudhair MBChB; Noor Abbas Hummadi Fayadh CABHS-RAD (SAGE Publishing, 2024)
Chronic recurrent multifocal osteomyelitis (CRMO) is a rare, non-infectious inflammatory disease with a prevalence of 1 to 2/10 6 , causing multiple lytic bone lesions. There are no established protocols for treating CRMO; thus, current practice is largely empirical. Data on the use of zoledronic acid (ZA) in juvenile CRMO are scarce. A 12-year-old male child with a history of multiple aseptic osteomylitis, affecting the chest wall, right ankle, and wrist, had no fever. Cultures and a bone biopsy ruled out infection or malignancy. The patient's condition stayed stable while taking naproxen (20 mg/kg/day) and methotrexate (10 mg/week) for 1.5 years until he experienced right elbow pain, swelling, no overlying skin erythema, and a restricted range of motion. The laboratory tests all came back normal, including white blood cell (WBC) count, erythrocyte sedimentation rate, C-reactive protein, and immunoglobin assays. The magnetic resonance imaging showed a focal lesion in the medial humeral condyle with increased signal intensity on T2 and short tau inversion recovery, mild joint effusion, and no cortical break. Thus, intravenous ZA infusion commenced at 0.0125 mg/kg initially, followed by 0.025 mg/kg 3 months later, with a marked improvement in the patient's clinical symptoms and radiological findings. Non-steroidal anti-inflammatory drugs and methotrexate were initially effective in treating our patient's condition, but a recurrence necessitated treatment modification. To the best of our knowledge, this case is the first documented instance of the use of ZA in CRMO in Iraq and Arab nations.